Epstein - Barr virus-associated lymphoepithelioma-like gastric carcinoma located on gastric high body: Two case reports - Yanfeng Bai; Qiqi Gao; Guoping Ren; Bo Wang; Hua Xiang (Wolters Kluwer Medknow Publications, 2014)
Lymphoepithelioma-like gastric carcinoma (LELGC) is a rare neoplasm of the stomach with an incidence of 1-4% of all gastric cancers. It is characterized by the presence of a lymphoid stroma with cells arranged primarily in micro alveolar, thin trabecular, and primitive tubular patterns or isolated cells. It is one of the histological patterns observed in patients with Epstein - Barr virus (EBV)-associated gastric carcinoma (EBVaGC). In situ hybridization was usually used to confirm the presence of EBV. There are two types of EBVaGC, LELGC, and ordinary type. Approximately, 15-25% of EBVaGC exhibit the LELGC pattern. Here, we described two cases of LELGC and the related literatures were reviewed as well. The two cases were submucosal mass from a 59- or 63-year-old man. We found LELGC has special clinicopathologic features and protein expression profile. This should promote us to make a true diagnosis.